The level of political activism among voters in selected barangays in Palo, Leyte. - Reglo, Jerome C.; Tamboong, Karah Jane A. (Jerome C. Reglo [and] Karah Jane A. Tamboong, 2010)
Palo is a third-class municipality, considered as the seat of Roman Catholicism in the Province of Leyte. Palo may be situated at the center of a rural-urban continuum. Hence, it is a very ideal locale for the study of political activism. Political activism refers to the extent of one's participation in political processes. In the context of this research, political activism entails participation in politically-related, cause-oriented, campaign-oriented, and civic-oriented activities.